Implementation of the Card Sort Method to Improve Student Learning Outcomes in Islamic Religious Education and Character Education at SMP Negeri Satu Atap Agusen - Damanik, Abdul Halim Agung Perkasa; Nazarniati (Jurnal Cendekia Islam Indonesia, 2025)
This classroom action research aimed to improve students’ learning outcomes in Islamic Education and Character Development (PAI & BP) through the application of the Card Sort learning method. The study was conducted at SMPN Satu Atap Agusen, located in Blangkejeren Subdistrict, during the 2019/2020 academic year, involving 32 students of class VIII-B. The research lasted for one month, from September 20 to October 20, 2019, and was carried out in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through observation, tests, and documentation, and analyzed using both qualitative and quantitative descriptive techniques. The results showed a significant improvement in students’ learning achievement after applying the Card Sort method. The average score in the pre-cycle was 58.18 with 30% mastery, which increased to 68.63 (55% mastery) in the first cycle and 83.63 (90% mastery) in the second cycle. These findings demonstrate that the Card Sort method effectively enhanced students’ engagement, collaboration, and understanding of Islamic moral values, leading to improved academic performance and active classroom participation.